Being in front of the patient. Nurse-patient interaction and use of technology in emergency services - Yeimy Yesenia Granados-Pembertty; María Mercedes Arias-Valencia (Universidad de Antioquia, 2013)
Objective. This study sought to describe how the use of technology intervenes in the nurse-patient relationship, from the nurse's point of view. Methodology. This was a qualitative research with tools from grounded theory. Twenty semi-structured interviews were conducted with nurses working in emergency services in three municipalities of Colombia. Results. Four categories emerged: 1) direct care, the maximum interaction or being in front of the patient; 2) fairly direct care; 3) indirect care, institutional management; and 4) minimum interaction; technology as facilitator of the interaction and awareness of the necessity for interaction. Conclusion. This study shows the irreplaceable nature of the nurse and the fundamental necessity of technology. The dual mediations of technology constitute a paradoxical matter that reveals the importance of placing it as a means; warning on the danger of converting it an end in and of itself.